Matemática e infância: o jogo na organização do ensino - Binsfeld, Carine Daiana (2019)
This work is the product of a Master’s Dissertation in Education inserted in Training, Knowledge and Professional Development research line, of the Graduate Program in Education of the Federal University of Santa Maria (UFSM), linked to the Group of Studies and Research in Mathematics Education (GEPEMat). On the assumption that human beings develop in their social relationships by appropriation of the culture historically produced, this research, in its guiding principles, is based on Historical-Cultural Theory (THC), Theory of Activity (TA), Teaching Guiding Activity (AOE) and understands that, in Early Childhood Education, when the game becomes a pedagogical resource, through the intentional organization of teaching by the teacher, it allows the development of higher psychological functions in children. Childhood Education is understood as a learning space that allows the child to grow, develop and produce culture, through experiences with scientific knowledge and, especially in this research, with mathematical knowledge. The overall objective of the research is to understand the learning of future teachers for Early Childhood Education, by organizing pedagogical games for the teaching of mathematics from the perspective of the Historical-cultural Theory. Such research was developed through the project "Mathematics in the Early Childhood Education? The game as guiding the Pedagogical Activity". A formative experiment was organized with four undergraduate students from the Pedagogy and Mathematics courses, who met in 15 formative meetings to study, discuss and develop learning situations in a preschool class with children. From 5 years old, in a public school in Santa Maria/RS. The executor principle of this research starts from the idea of understanding the phenomenon in its totality; Thus, the data - provided by written reports, reflective discussions, field diary and recorded and photographed records- were presented through episodes and studied from four units of analysis. The relationships established between them indicate that future teachers, by appropriating a general way of organizing teaching, taking the game as a starting point in the organization of actions, may be learning about the teaching work. This movement was mediated by the intentional organization of the formative experiment. Thus, the future teacher, when organizing pedagogical games for the teaching of mathematics in Early Childhood Education, supported by a theoretical reference that sustains his practice in a shared formation, appropriates knowledge about the organization of teaching through the game, understood as the activity that best enables the child to develop the higher psychological functions towards the development of theoretical thinking and places himself in the process of meaning of his teacher education.